Influencia del sistema integrado de administración financiera en la ejecución de recursos públicos de la Municipalidad Provincial de Maynas 2023 - Heredia García, Juan Pablo (2025)
The main purpose of the study was to analyze the influence of the integrated financial management system on the execution of public resources in the Provincial Municipality of Maynas 2023. This was an applied research project, as it not only describes but also exhaustively details the connection between the variables studied. The population and sample consisted of 55 employees. A survey technique was used to collect the data, using a questionnaire as an instrument. The findings revealed that the IFMIS significantly influences the execution of public resources. Specifically, a Spearman's Rho correlation coefficient of (0.328) was identified, with a p-value of (0.015) at a significance level of 5% (two-tailed), confirming the statistical significance of this impact. In conclusion, a significant influence was determined between the IFMIS and the execution of public resources.